Performance Enhancement of an a-Si:H/μc-Si:H Heterojunction p-i-n Solar Cell by Tuning the Device Parameters (Dhaka University Journal of Science, 2021)
In this work, the solar cell design parameters like- layer thickness, bandgap, donor and acceptor concentrations are varied to find optimum structure of a hydrogenated amorphous silicon (a-Si:H) and hydrogenated microcrystalline silicon (μc-Si:H) heterojunction p-i-n solar cell. A thin a-Si:H p-layer of 1 to 5 nm followed by a thick a-Si:H i-layer of thickness 1400 to 1600 nm and then thin n-layer of thickness 1 to 5 nm with acceptor concentration of 102 cm−3 and donor concentration of 1020 cm−3 and the bandgaps of p-, i-, and n- layers with higher bandgaps closer to 2.2 eV for a-Si:H p-layer, 1.85 eV for a-Si:H i-layer, and 1.2 eV for μc-Si:H n-layer have showed better performances. The optimum cell has a JSC of 18.93 mA/cm2, VOC of 1095 mV, Fill factor of 0.7124, and efficiency of 14.77%. The overall external quantum efficiency of the numerically designed cell also remained very high from 85-95 % for wavelengths of 300-650 nm range. This indicates that the device will perform its best under both high and low frequency i.e. ultra-violet, near visible and visible light wavelengths.Dhaka Univ. J. Sci. 69(2): 88-95, 2021 (July)